2020
DOI: 10.1123/mc.2018-0098
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor Strategies in Individuals With Poststroke Hemiparesis When Standing Up Without Vision

Abstract: This study investigated the sensorimotor strategies for dynamic balance control in individuals with stroke by restricting sensory input that might influence task accomplishment. Sit-to-stand movements were performed with restricted vision by participants with hemiparesis and healthy controls. The authors evaluated the variability in the position of participants’ center of mass and velocity, and the center-of-pressure position, in each orthogonal direction at the lift-off point. When vision was restricted, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
2
1
Order By: Relevance
“…21,25 Moreover, the CoP-ML variability decreased while CoP-AP increased in hemiparesis conditions accompanied by restricted vision but not healthy controls. 26 However, our results suggested that the USN model conditions generally produced more reliable CoP measures than non-USN conditions during tests.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…21,25 Moreover, the CoP-ML variability decreased while CoP-AP increased in hemiparesis conditions accompanied by restricted vision but not healthy controls. 26 However, our results suggested that the USN model conditions generally produced more reliable CoP measures than non-USN conditions during tests.…”
Section: Discussioncontrasting
confidence: 56%
“…Besides, beyond our current CoP testing paradigm, while taking into account the validity and reliability findings of this study, sensorimotor adaptation also needed to consider before mimicking movement in healthy individuals. 13,26 As a fundamental study, the translation of our work into clinical practice was to propose using this model in healthy participants to develop new assessment and treatment simulation feasibility in further preliminary trials, in the framework to understand physiological effects to improve neglect symptoms, including postural balance, before applied in the neuro-rehabilitation context with minimal risks. 13,14 The present study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The pathological dysfunction in the sensory-motor circuitry contributes to the loss of balance function ( Darbin et al, 2016 ; Kuramatsu et al, 2021 ). However, the compensatory mechanism for somatosensory conditions by visual information completes sit-to-stand in patients after stroke ( Kuramatsu et al, 2020 ). Like sit-to-stand, patients after stroke would be able to adapt gait function on an uneven surface.…”
Section: Introductionmentioning
confidence: 99%